Marital Rape As A Crime Of Sexual Violence In Positive Law In Indonesia - Eva Khumairoh; Ishaq Ishaq; Muhammad Faisol (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Rape in a relationship has similar effects to rape outside of marriage. It is intended to avoid unnatural sexual behavior in a couple. Although men are considered to have full rights over their wives including in terms of sexual relations, it can worsen the relationship. The problem raised in this paper is to find out how the regulation of marital rape in Indonesia. The research method used is normative legal research, in order to analyze the vague norms related to marital rape in Law No. 23 Thn. 2004 with Law No. 12 of 2022. With the results of the analysis explaining that the factor of marital rape which later became a serious case both in the national and international scope needs regulations on marital rape, especially in Indonesia as a form of affirmation in the gander structure.